Experiências do sagrado: fabulações de um Reinado em A coroação de uma rainha - Rafael Antônio Motta Böeing (2016)
This paper aims to think about the mise-en-scène of religious experiences of Congadas, or Reinados, on film documentary, featuring the movie The coronation of a Queen (1993), directed by Arthur Omar. Recognizing a very particular movie among the set of documentaries that film these traditions, the paper approach this title to discuss ways of staging afro-brazilian religious traditions which avoid the cultural heritage perspective (as we notice today on official documentation about their celebrations, expressions and knowledge), proposing other forms of translations, in respect for their memory and their temporality. For that reason, our analysis focus mainly on the effects of translation produced by an specific aesthetic proposal when it points to the rites, myths and cosmology of the Reinado of Our Lady of the Rosary of Jatobá. Considering that this translation implies an affectation by thefilmed world, the work applies the concept of confabulation to the analysis. Through this concept, we seek to apprehend the bodies, faces, objects, sounds and movements of Congadas that acquire a fictional power, as well as the filmic resources that reverberate, intensify and double that power, engendering what we identify as free indirect subjectivities. Therefore, three analytical axes - temporality, musicality and materialities - guide the work, directing our gaze at the various segments in the way to understand this permeability between montage, soundtrack, camera and the religious experiences of Congadas. Simultaneously, we call up the movies Salve Maria (Junia Torres, Pedro Portella and Aparecida Reis, 2006) and Reis negros (Rodrigo Campos, 2005) for a dialogue with Arthur Omars title, as they offer usother perspectives on these same experiences.